2009
DOI: 10.1200/jco.2008.17.1561
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Rituximab After Cyclophosphamide, Vincristine, and Prednisone Prolongs Progression-Free Survival in Advanced Indolent Lymphoma: Results of the Randomized Phase III ECOG1496 Study

Abstract: The E1496 study provides the first phase III data in untreated indolent lymphoma that MR after chemotherapy significantly prolongs PFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
142
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(149 citation statements)
references
References 24 publications
7
142
0
Order By: Relevance
“…Other randomized trials also failed to directly demonstrate a translation from improved outcome in terms of EFS to a prolonged OS. 23 However, recent cross-trial comparisons indicated steady progress in OS for patients with FL in part due to improved front-line therapies. [11][12][13] This clearly suggests that phase III trials with a PFS or EFS end point, such as the FL2000 study, were likely underpowered to demonstrate a significant OS prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…Other randomized trials also failed to directly demonstrate a translation from improved outcome in terms of EFS to a prolonged OS. 23 However, recent cross-trial comparisons indicated steady progress in OS for patients with FL in part due to improved front-line therapies. [11][12][13] This clearly suggests that phase III trials with a PFS or EFS end point, such as the FL2000 study, were likely underpowered to demonstrate a significant OS prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…The CVP chemotherapy used during the time these samples were collected is no longer the standard of care. The monoclonal antibody rituximab (45) is now used with current chemotherapy strategies (46,47). CD20, the rituximab target, tends to be underexpressed on the LNP cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several schedules have been proposed for maintenance therapy, with either 4 weekly infusions every 6 months (one, two or four times) or one infusion every 2 or 3 months [20]. The benefits in terms of progression-free survival and overall survival of rituximab maintenance were shown in several trials [17,18,21,22] and in a recent meta-analysis [23]. Rituximab was therefore approved by the FDA in 2011 for first-line maintenance treatment of patients with advanced FL who responded to initial treatment with rituximab.…”
Section: Introductionmentioning
confidence: 99%